A Study on the Impact of Influencer Marketing on Consumer Purchase Decisions at Tulip Garden, Yavatmal - Nitnaware, Nishika Vinod; Tekade, Atul (Journal of Neonatal Surgery, 2025)
The increasing role of digital marketing, particularly influencer marketing, has reshaped consumer behavior and purchasing patterns. Influencers, with their vast reach and ability to engage with audiences, have become essential tools for brands to influence potential customers. The study aims to analyse the impact of influencer marketing on consumer purchase decisions, specifically focusing on Tulip Garden in Yavatmal. Through surveys conducted among 100 participants, the research explores how various types of influencers, content formats, and platforms affect consumer perceptions and behavior. The findings reveal a significant correlation between influencer recommendations and consumer decisions, with Instagram being the most preferred platform for such marketing strategies. The study also highlights the importance of trust and authenticity in influencer-consumer relationships, as these factors are critical in driving engagement and influencing purchases. The research emphasizes the need for brands to select influencers that align with their values and target demographics to ensure effective marketing. Additionally, it identifies the challenges businesses face, such as the authenticity of endorsements and the growing skepticism towards influencer promotions. Recommendations include adopting data-driven approaches to monitor influencer performance and ensuring transparency in influencer partnerships to maintain consumer trust. Overall, the study provides valuable insights for brands seeking to leverage influencer marketing to drive sales and foster long-term consumer loyalty.